2003
DOI: 10.1046/j.1524-4741.2003.09207.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Prognostic Significance of HER-2 Expression in Breast Cancer According to Tumor Size

Abstract: The prognostic importance of HER-2 status in breast cancer has been investigated extensively, but findings have not been uniform across immunohistochemical studies using fixed, paraffin-embedded specimens. We speculate that studies with an overrepresentation of large tumors might not produce evidence for an independent effect of a single marker because breast tumors of larger size tend to exhibit multiple adverse attributes as the malignancy advances through the metastatic cascade. Further, it has been posited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…We stratified analyses a priori by SEER summary stage of disease (local, regional, distant) because of the mixed evidence of prognostic value of HER2 status in node-negative patients. 28 Two forced models were constructed using the same variables included in the logistic regression. Survival time among patients who died was defined as months from date of diagnosis to date of death.…”
Section: Methodsmentioning
confidence: 99%
“…We stratified analyses a priori by SEER summary stage of disease (local, regional, distant) because of the mixed evidence of prognostic value of HER2 status in node-negative patients. 28 Two forced models were constructed using the same variables included in the logistic regression. Survival time among patients who died was defined as months from date of diagnosis to date of death.…”
Section: Methodsmentioning
confidence: 99%
“…To date, no universally accepted markers for this group of patients have been isolated [5,20]. Recently, HER2/neu expression has attracted significant interest as a potential prognostic and [20,21]. In general, HER2/neu overexpression is correlated with tumor size or number of involved LNs and is more often observed in advanced breast cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, HER2/neu expression has attracted significant interest as a potential prognostic and [20,21]. In general, HER2/neu overexpression is correlated with tumor size or number of involved LNs and is more often observed in advanced breast cancer [21]. Several studies support the prognostic significance of HER2/neu in LN-positive breast cancer [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…35,36 The value of HER-2 amplification or overexpression as an independent prognostic factor in node-negative cases remains controversial. [37][38][39][40] Some authors have suggested that its prognostic significance seems to increase in lymph node-positive patients, 9 while others showed that HER-2/neu amplification identifies a poor prognosis in node-negative breast cancer. 38,41 In our study, we considered both lymph node-negative and -positive (metastatic) cases.…”
Section: Discussionmentioning
confidence: 99%
“…4 HER-2/neu amplification or overexpression is found in approximately 20% to 40% of primary invasive breast cancer cases. [5][6][7][8][9] It is possible to study both protein expression and gene amplification. The most common techniques are, respectively, immunohistochemistry and fluorescence in situ hybridization (FISH).…”
mentioning
confidence: 99%